Peran Komunikasi Asertif dalam Hubungan Kerja yang Positif dan Produktif - April Laksana; Deden Deden; Ilham Arifin; Rifqi Hibatullah; Muhammad Salim Albana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Assertive communication plays a key role in building positive and productive working relationships in an organization. This research aims to explore the influence of assertive communication on work effectiveness and productivity in the context of work relations in companies. The method used in this research is a qualitative approach by collecting data through interviews and observations in various organizations. The research results show that assertive communication, which prioritizes respect for the rights and feelings of other people while expressing opinions openly and firmly, can reduce conflict, increase cooperation, and improve the work atmosphere. Apart from that, assertive communication also contributes to reducing stress, increasing self-confidence, and clarifying expectations between team members. By implementing assertive communication techniques, such as active listening, stating expectations clearly, and providing constructive criticism, work productivity in an organization can increase significantly. This research provides recommendations for organizations to develop assertive communication skills among all members to create a more harmonious work environment and support the achievement of common goals.